Answer:
10017
Step-by-step explanation:
10^(4)-\sqrt(121)+3^(3)+4^(0)
So, 3^3= 27
4^0=1
10^4=10,000
-square 121= -11
So now you got:
10,000-11+27+1
=10017
Answer:
d. 32.9
Step-by-step explanation:
To find c, we'll use the Law of Sines that says:
![\frac{a}{sin(A)} = \frac{c}{sin(C)}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%7D%7Bsin%28A%29%7D%20%3D%20%5Cfrac%7Bc%7D%7Bsin%28C%29%7D)
And we'll isolate a to get:
![c = \frac{sin(C) * a}{sin(A)}](https://tex.z-dn.net/?f=c%20%3D%20%5Cfrac%7Bsin%28C%29%20%2A%20a%7D%7Bsin%28A%29%7D)
We first need to find A, which is easy. The sum of the interior angles of a triangle is 180 degrees... and we already have 2 of them, so:
A = 180 - 90 - 47.3 = 42.7
(converted 47°18' to 47.3)
Then we will plug-in the information we already have
![c = \frac{sin(90) * 22.3}{sin(42.7)} = 32.88](https://tex.z-dn.net/?f=c%20%3D%20%5Cfrac%7Bsin%2890%29%20%2A%2022.3%7D%7Bsin%2842.7%29%7D%20%3D%2032.88)
So, let's round it to 32.9 to match the answer number D.
Answer:
63=x*y
Step-by-step explanation:*
y = 7 x=1. so 9 will muiltiply 7 until there is 9 7s then you got the answer
Answer:
x= -2y/3
-4y+4y=14
0y= 14
This has no solution.
Step-by-step explanation:
Answer In cases of two equations having two unknown variables the simultaneous method of solving the equations is adopted.
Supposing “0” as the value of “k” we will have the equation as 3x+2y=0
Then separating variable x will give, x= -2y/3
Substituting the value of x into the first equation that is: 6x + 4y = 14
6(-2y/3)+4y=14
Expanding this we get: 6(-2y/3)+4y=14
-4y+4y=14
0y= 14
Thus, no solution.